Marchiafava-Bignami disease presenting as reversible coma. Issue 4 (4th April 2022) - Zhang, Yixin; Culpepper, Kaleb; Mathew, Reshmi; CruzSaavedra, Luis
Abstract : Marchiafava-Bignami disease (MBD) is a rare demyelinating condition of the corpus callosum and subcortical white matter that is most commonly seen in alcoholic patients. The course of the disease varies with symptoms that range from dementia to complete coma; severe intermittent sympathetic storming with abnormal posturing is often reported in literature. It is presumably secondary to a deficiency of B complex vitamins, specifically thiamine and many patients have clinical improvement after repletion of B vitamins. We present a case of a 35-year-old man who developed MBD secondary to polysubstance misuse without history of alcohol use. His clinical course was complicated by persistent comatose state with autonomic dysfunction. After the administration of high-dose thiamine and vitamin C and E, the patient regained consciousness and was able to follow commands within 48 hours. Furthermore, this case showed recognising brain MRI findings for MBD is a crucial step in disease identification.